(untitled) (Journal of Laboratory Animal Science, 2024)
A six-year-old female bonnet monkey was noticed with a bloated abdomen seven days after experimentation. A plain radiograph was taken to determine the cause of bloating. However, the plain radiograph did not reveal any significant changes except patches of gas in the abdomen. Hence, a contrast radiograph was done with a barium meal. A constriction was observed in the rectal region in contrast radiograph. An emergency laparotomy was done and stricture was surgically corrected by an end-to-end anastomosis.